The Khamkhains, Neurotrophic Drimane-Type Sesquiterpenoids Derived from a Polyporaceous Basidiomycete Originating from Thailand - Paomephan, Pathompong; Hassan, Khadija; Kirchenwitz, Marco; Pfütze, Sebastian; Surup, Frank; Císařová, Ivana; Boonchird, Chuenchit; Stadler, Marc (Journal of natural products, 2025)
Eight unprecedented terpenoids were isolated from submerged cultures of a polyporoid basidiomycete originating from Thailand (which had been referred to as "Cerrena sp." in a previous publication) by preparative chromatography. Their chemical structures were elucidated by extensive two-dimensional nuclear magnetic resonance (NMR) spectroscopy and high-resolution mass spectrometry. One of the compounds was crystallized, and its absolute configuration was established by X-ray crystallography. Among the isolated metabolites were several members of the rare nitrogen-containing drimane type and one dimeric drimane, which consists of a nitrogen-containing monomer and a regular monomer. The latter compound represents a hitherto unknown type of terpenoid natural product. The metabolites were subjected to a biological characterization, and some of them showed significant neurotrophic effects. Notably, several of the compounds significantly enhanced the outgrowth of neurites in PC12 cells when treated with 5 ng/mL nerve growth factor. On the other hand, they were devoid of significant cytotoxic and antimicrobial effects.
Keywords: Thajsko; Sesquiterpenes; Neurites; buňky PC12; Thailand; Rats; Polycyclic Sesquiterpenes; PC12 Cells; molekulární struktura; Molecular Structure; Animals; seskviterpeny; zvířata; Basidiomycota; krystalografie rentgenová; neurity; Crystallography, X-Ray; krysa rodu Rattus; polycyklické seskviterpeny